Current applications of high-intensity ultrasound with microbial inactivation or stimulation purposes in dairy products. (December 2021) - Guimarães, Jonas T; Scudino, Hugo; Ramos, Gustavo LPA; Oliveira, Gabriella AR; Margalho, Larissa P; Costa, Leonardo EO; Freitas, Mônica Q; Duarte, Maria Carmela KH; Sant'Ana, Anderson S; Cruz, Adriano G
Highlights: Effects of high-intensity ultrasound with microbial purposes were approached. Mechanism of action of different ultrasonic intensities were explained. The use of different energy measurements to explain the US effects was discussed. Current applications in dairy products were presented. Abstract : Emerging technologies are being constantly improved, giving rise to new processes capable of promoting greater nutritional preservation and improved technological characteristics, in addition to the benefits related to energy efficiency. Ultrasound treatment has stood out among the non-thermal technologies, due to several benefits related to microstructural changes and microbial inactivation. The study of this technology is particularly important in dairy products, which represent one of the most important segments of the food industry and have a wide range of products developed from different processes. It has been shown that depending on the applied ultrasound treatment intensity (combination of frequency, power, processing time and sample volume) and the resulted temperature, the treatment may exert opposite effects on the food products, such as inactivation/stimulation of microorganisms and enzymes. Therefore, the purpose of this review was to contextualize the different applications and mechanism of action of ultrasound in milk and dairy products, approaching the technological benefits from the microbiological point of view.